The Impact of Social Support for Women on Supporting Entrepreneurship for Saudi Women (An Empirical Study on the City of Abha) - Alsagoor, Areej Hassan; Alamri, Amal Dafer; Sultan, Amal Yahya; Alalkami, Aisha Abdalrahman; Alzahrani, Mariam Abdullah; Alhudaithy, Abdullatif Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
The current study aimed to identify the impact of social support for women on supporting entrepreneurship for Saudi women, through: identifying the level of social support and the level of entrepreneurship among female entrepreneurs in the city of Abha. revealing the existence of a statistically significant correlation between social support and entrepreneurship among Female entrepreneurs in the city of Abha. revealing that there are statistically significant differences in social support and entrepreneurship among female entrepreneurs in the city of Abha due to the study variables (social status - age - number of children - qualification - type of activity). To achieve this goal, the study used the descriptive analytical method, and the questionnaire as a tool for data collection, and the study community represented all women entrepreneurs in the city of Abha, and a random sample of (409) women entrepreneurs in the city of Abha was chosen. The study reached several results, the most important of which are: The level of social support for female entrepreneurs in the city of Abha came to a medium degree. the level of application of the principles of entrepreneurship among female entrepreneurs in the city of Abha came to a large degree. the economic and social return of entrepreneurship projects came to a large degree. There is a statistically significant correlation between social support and entrepreneurship among female entrepreneurs in the city of Abha, there are no statistically significant differences between the responses of the study sample according to the variable of social status - age - number of children - qualification, while there are differences according to the variable type of activity in favor of agricultural category. the study recommends the necessity of spreading an entrepreneurial culture among Saudi women in a way that contributes to increasing the number of female entrepreneurs and contributes to enhancing the national economic and social return. the need to organize national initiatives to meet the needs of women entrepreneurs and work to solve the problems they face, and the need to pay attention to providing Advanced training programs on entrepreneurship and the areas needed by the Saudi labor market, which contribute to providing new entrepreneurial opportunities.
Keywords: entrepreneurship; social support; Saudi women; female entrepreneurs